Hybrid Technique of Lamellar Keratoplasty (DMEK-S) - Pavel Studeny; Deli Sivekova; Katerina Liehneova; Magdalena Vokrojova; Pavel Kuchynka (Journal of Ophthalmology)
Purpose: To evaluate the outcomes of the hybrid technique of posterior lamellar keratoplasty (DMEK-S). Materials and Methods: 71 eyes of 55 patients enrolled in a single-center study underwent posterior lamellar keratoplasty with a hybrid lamella DMEK-S implanted using a solution implantation technique, owing to endothelial dysfunction. The outcome measures studied were visual acuity and endothelial cell density. Results: The rate of endothelial cell loss caused by surgery was 43.8%. During followups, we observed the stabilization of postoperative findings, or at minimum a very low rate of corneal endothelial cell loss. The UCDVA and BCDVA dramatically improved postoperatively. The rebubbling rate in our group of patients was 61.9%. We replaced the lamella due to its failure or malfunction in 17 patients (23.9%). Conclusion: In summary, DMEK-S combines the advantages of DSEK/DSAEK and DMEK. The central zone of bare Descemet’s membrane and endothelium allows for very good visual outcomes, and the peripheral rim allows for better manipulation of the lamella during implantation. It is an effective method of treating the endothelial dysfunction of various etiologies, but the high complication rate needs to be addressed before widespread implementation of the technique in the future.